Literature Review: Obstacles in Implementation of Chronic Disease Management Program (Prolanis) in Public Health Centers - Nifta Salsabilah, Ersa; Aan Adriansyah, Agus; Jannatul Firdausi, Nurul; Handayani, Dwi (Rifa'Institute, 2023)
Introduction: BPJS Kesehatan created a chronic disease management program (Prolanis) to prevent complications of chronic diseases. But in fact, the implementation of prolanis is still not running optimally as evidenced by this activity has not shown a good impact on the community. Objective: This review literature aims to identify constraints in the implementation of chronic disease management programs (Prolanis) at the Center for Public Health. Method: This study is a literature review. The data sources used are from google scholar and garuda portals in the 2017-2022 times frame. The keywords used are constraints, chronic disease management programs, prolanis, Public Health Centers. Result and Discussion: The results of the study showed 10 aspects of communication, namely lack of coordination, clarity in delivering success indicators, and lack of socialization. The human resources aspect of 12 articles is the lack of quantity and quality of officers. The funding aspect was obtained by 12 articles, namely the process of submitting and disbursing old claims and withdrawing service fees. Conclusion: from this literature review, it is found that the implementation of the Center for Public Health in implementing the prolanis program in Indonesia has not run optimally. Advice improves routine health promotion every month